Pancreatic Organoids for Regenerative Medicine and Cancer Research - Casamitjana, Joan; Espinet, Elisa; Rovira, Meritxell (Frontiers in Cell and Developmental Biology, 2022)
In recent years, the development of ex vivo organoid cultures has gained substantial attention as a model to study regenerative medicine and diseases in several tissues. Diabetes and pancreatic ductal adenocarcinoma (PDAC) are the two major devastating diseases affecting the pancreas. Suitable models for regenerative medicine in diabetes and to accurately study PDAC biology and treatment response are essential in the pancreatic field. Pancreatic organoids can be generated from healthy pancreas or pancreatic tumors and constitute an important translational bridge between in vitro and in vivo models. Here, we review the rapidly emerging pancreatic organoid model and summarize the current applications of the technology on tissue regeneration, disease modelling, and drug screening.